Environmental sustainability from anesthesia providers’ perspective: a qualitative study - Greta Gasciauskaite; Justyna Lunkiewicz; Donat R. Spahn; Corinna Von Deschwanden; Christoph B. Nöthiger; David W. Tscholl (BMC Anesthesiology, 2023)
Abstract Background The world faces a significant global health threat – climate change, which makes creating more environmentally sustainable healthcare systems necessary. As a resource-intensive specialty, anesthesiology contributes to a substantial fraction of healthcare’s environmental impact. This alarming situation invites us to reconsider the ecological health determinants and calls us to action. Methods We conducted a single-center qualitative study involving an online survey to explore the environmental sustainability from anesthesia providers’ perspectives in a center implementing internal environmentally-sustainable anesthesia guidelines. We asked care providers how they perceive the importance of environmental issues in their work; the adverse effects they see on ecological sustainability in anesthesia practice; what measures they take to make anesthesia more environmentally friendly; what barriers they face in trying to do so; and why they are unable to adopt ecologically friendly practices in some instances. Using a thematic analysis approach, we identified dominating themes in participants’ responses. Results A total of 62 anesthesia providers completed the online survey. 89% of the participants stated that environmental sustainability is essential in their work, and 95% reported that they implement measures to make their practice greener. A conscious choice of anesthetics was identified as the most common step the respondents take to reduce the environmental impact of anesthesia. Waste production and improper waste management was the most frequently mentioned anesthesia-associated threat to the environment. Lacking knowledge/teaching in sustainability themes was recognized as a crucial barrier to achieving ecology goals. Conclusions Sustainable anesthesia initiatives have the potential to both encourage engagement among anesthesia providers and raise awareness of this global issue. These findings inspire opportunities for action in sustainable anesthesia and broaden the capacity to decrease the climate impact of health care.